A review on biosynthesis of silver nanoparticles and their biocidal properties - Siddiqi, Khwaja Salahuddin; Husen, Azamal; Rao, Rifaqat A. K. (Journal of nanobiotechnology, 2018)
Use of silver and silver salts is as old as human civilization but the fabrication of silver nanoparticles (Ag NPs) has only recently been recognized. They have been specifically used in agriculture and medicine as antibacterial, antifungal and antioxidants. It has been demonstrated that Ag NPs arrest the growth and multiplication of many bacteria such as Bacillus cereus , Staphylococcus aureus , Citrobacter koseri , Salmonella typhii , Pseudomonas aeruginosa , Escherichia coli , Klebsiella pneumonia, Vibrio parahaemolyticus and fungus Candida albicans by binding Ag/Ag + with the biomolecules present in the microbial cells. It has been suggested that Ag NPs produce reactive oxygen species and free radicals which cause apoptosis leading to cell death preventing their replication. Since Ag NPs are smaller than the microorganisms, they diffuse into cell and rupture the cell wall which has been shown from SEM and TEM images of the suspension containing nanoparticles and pathogens. It has also been shown that smaller nanoparticles are more toxic than the bigger ones. Ag NPs are also used in packaging to prevent damage of food products by pathogens. The toxicity of Ag NPs is dependent on the size, concentration, pH of the medium and exposure time to pathogens.